Informática educativa : perspectiva de qualificação do diálogo pedagógico - Lorençatto, Mauro (2007)
This project shows a research experiment of interaction between teachers, students and technologies according to the development of a project in a school in the city of Santa Rosa RS-Brazil. The research verifies how the dialogical relationships are established between teachers and students and between students facing the use of computer in pedagogical activities. We should understand as pedagogical dialog the interaction of meanings between teachers and students and among students which offer an educational emancipation, because the learning-teaching process. On the other hand the information and communication technologies need a proper environment for the pedagogical appropriation of teachers and students, seeking the overcoming of the computer at school myth. In other words overcome the illusion that the presence of computer would solve all the school pedagogical problems. Moreover, it happened at the educational computer class (ECC), with students from the first high school grades and by the researcher-teacher, and observation field job, methodologically organized in four steps: first one, meetings were done for the project definition and actions planning; on a second moment, a field research was done with the collecting of the information and images from the Sanga do Inácio and testimony from some of the people who live on the shores. The third action was to separate the most important data collected and a multimedia presentation was created about the Sanga do Inácio reality; on the fourth and last step, a project evaluation was made through a discussion and a questionnaire proposed by the researcher-teacher to the students who had participated on the project. The testimonies show a huge satisfaction on the interactions between teacher, students and technologies throughout the project development, what take us to confirm that the use of information and communication qualifies the pedagogical dialog